Biomarkers: evaluation of clinical utility in surveillance and early diagnosis for hepatocellular carcinoma - Song, Peipei; Tang, Qi; Feng, Xiaobin; Tang, Wei (Scandinavian journal of clinical & laboratory investigation. Supplement, 2016)
Hepatocellular carcinoma (HCC) is the fifth most common cancer and the second most common cause of death from cancer worldwide. Strategies to surveil and diagnose HCC in an earlier stage are urgently needed since this is when curable interventions can be offered to achieve long-term disease-free survival. Over the past few decades, research has suggested measuring alpha-fetoprotein (AFP) concentration and performing abdominal ultrasound (US) as part of routine surveillance of HCC every 6 months for high-risk patients, and many HCC guidelines worldwide have also recommended these examinations. Over the past 5 years, however, the role of serum biomarkers in HCC surveillance and diagnosis has diminished due to advances in imaging modalities. AFP was excluded from the surveillance and/or diagnostic criteria in the HCC guidelines published by some Western countries. In Asian countries, serum biomarkers such as AFP, the Lens culinaris agglutinin-reactive fraction of AFP (AFP-L3), and des-γ-carboxyprothrombin (DCP) are still recommended for HCC surveillance and are being used as an adjunctive diagnostic tool in accordance with HCC guidelines. Moreover, novel biomarkers including Dickkopf-1 (DKK1), midkine (MDK), and microRNA (miRNA) are being studied in this regard. China accounts for 50% of HCC cases worldwide, so identifying biomarkers of HCC is paramount. Recent studies have indicated the clinical utility of simultaneous measurement of AFP and DCP for the early detection of HCC in China. They are predominantly used for cases caused by HBV infection. Additional large-scale prospective studies should be conducted to establish the utility of these biomarkers.